Pengaruh Produk, Promosi, dan Pelayanan Terhadap Kepuasan Nasabah Menggunakan Produk Asuransi Takaful Dana Pendidikan (Studi Kasus pada PT. Asuransi Takaful Keluarga Di Medan) - MUhammad Azrai Nasution; M Marliyah; M. Ridwan (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara Medan, 2019)
The number of takaful insurance customers is decreasing every year. This can be caused by the level of customer satisfaction that can be influenced by product factors, promotions, and services. The purpose of this study was to analyze the influence of products, promotions, and services on customer satisfaction using educational fund takaful insurance products. This research is quantitative research. This research was conducted at PT. Asuransi Takaful Keluarga Medan with a sample of 70 respondents. The instrument used to obtain data is a questionnaire using a Likert scale. Data analysis techniques with OLS (Ordinary Least Square) analysis are supported by classical assumption tests, multiple regression analysis, t-test and f-test using the Eviews application. The results of this study indicate that simultaneously, product, promotions, and services influence customer satisfaction and partially only promotional variables that do not affect customer satisfaction. Thus, Asuransi Takaful Keluarga Medan should maintain the strategy that has been implemented and increase promotional activities to be able to achieve the company's target in increasing customer satisfaction.